Perancangan Sistem Informasi Penilaian Kinerja Guru Di SMK Negeri 10 Bungo - Lamsari Harahap; Faiza Rini; Haris Kurniawan (Justek : Jurnal Sains dan Teknologi, 2025)
Abstract:  The teacher performance evaluation process at SMK Negeri 10 Bungo has so far been carried out manually, which results in the process taking a relatively long time and the resulting data is difficult to use for continuous performance evaluation. This poses a challenge in ensuring that the teacher performance evaluation process is carried out efficiently, quickly, and accurately Therefore, this study aims to design a systematic and computerized teacher performance assessment information system using the System Development Life Cycle (SDLC) method. This research was conducted using Visual Studio Code as the development editor and the PHP 8 programming language. The results of this study are the Design of a Teacher Performance Assessment Information System with an iterative model consisting of six stages: planning, analysis, design, implementation, testing, and management. System testing is divided into two stages, namely Alpha testing (which includes whitebox and blackbox testing) and Beta testing by experts and users. The results of the Beta test show that the validation carried out by system experts obtained an average score of 88.5%, with the description "very good." Meanwhile, the user assessment questionnaire involving admins, principals, and teachers obtained an average score of 81%, also with the description "very good.". Abstrak: Penelitian ini bertujuan untuk merancang sistem informasi penilaian kinerja guru yang sistematis dan terkomputerisasi dengan menggunakan metode System Development Life Cycle (SDLC). Penelitian ini dilakukan dengan menggunakan Visual Studio Code sebagai editor pengembangan dan bahasa pemrograman PHP 8. Hasil dari penelitian ini adalah Perancangan Sistem Informasi Penilaian Kinerja Guru dengan model iteratif yang terdiri dari enam tahapan: perencanaan, analisis, desain, implementasi, pengujian, dan pengelolaan. Pengujian sistem dibagi menjadi dua tahap, yaitu pengujian Alpha (yang meliputi pengujian whitebox dan blackbox) dan pengujian Beta oleh tenaga ahli dan pengguna. Hasil pengujian Beta menunjukkan bahwa validasi yang dilakukan oleh tenaga ahli sistem memperoleh nilai rata-rata 88,5%, dengan keterangan "sangat baik." Sementara itu, angket penilaian pengguna yang melibatkan admin, kepala sekolah, dan guru memperoleh nilai rata-rata 81%, juga dengan keterangan "sangat baik."